Case Report: Endovascular thrombectomy for acute ischemic stroke with bilateral internal carotid artery fibromuscular dysplasia - Zheng, Zhi; Yang, Chen; Meng, Xufeng; Yang, Li; Hao, Yunfei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFibromuscular Dysplasia (FMD) is a rare, idiopathic, non-inflammatory, and non-atherosclerotic disease that often presents with stenosis of medium or small arteries, potentially leading to acute cerebral infarction. Due to its atypical symptoms, FMD is prone to being missed or misdiagnosed, and the optimal treatment strategy for patients with acute cerebral infarction accompanied by FMD remains unclear.Case descriptionA 41-year-old male patient presented to the emergency department with right-sided limb weakness and slurred speech for 4 h. He had a history of gout and smoking. Physical examination revealed grade 2 muscle strength in the right limb and a NIHSS score of 15. Head CT showed an acute cerebral infarction in the left temporal and parietal lobes. Cerebral angiography revealed “string-of-beads” stenosis of the bilateral internal carotid arteries (multifocal fibromuscular dysplasia), occlusion of the left internal carotid artery (ICA) at its origin (TICI grade 0), and a dissecting aneurysm in the C1 segment. After comprehensive assessment, the patient was diagnosed with ICA fibromuscular dysplasia and underwent emergency endovascular mechanical thrombectomy. Intraoperatively, tirofiban was used for anti-thrombotic therapy, and postoperative management included aspirin and statin therapy for secondary prevention. Follow-up cerebral angiography at 1 and 3 months showed patency of the left ICA, with a Modified Rankin Scale (mRS) score of 1, and no new ischemic events.ConclusionFMD is a rare non-atherosclerotic disease, with cerebral vessel involvement being relatively common and presenting a variety of clinical symptoms, which poses challenges in diagnosis and treatment. For patients with FMD accompanied by acute vascular occlusion, endovascular mechanical thrombectomy is an effective treatment option, and in terms of treatment strategy, combining anti-platelet therapy can effectively improve neurological function and achieve a favorable prognosis.